Cavitation characteristics around a sphere: An LES investigation. (January 2018) - Pendar, Mohammad-Reza; Roohi, Ehsan
Highlights: LES Investigation of cavitating flow around sphere. Providing a thorough understanding of the fluid dynamics of sphere cavitation. Reporting vortex shedding, velocity fluctuation, and cavity evolution. Abstract: Here we examine partial and supercavitation over a sphere at a constant Reynolds number of 1.5 × 10 6 and a broad range of cavitation numbers (0.36 <σ< 1). Large eddy simulation (LES) and Sauer mass transfer model were used to simulate the dynamic and unsteady cavitation around the sphere. Also, the compressive volume of fluid (VOF) method is used to track the cavity interface. The two-phase flow solver of the OpenFOAM package, intephaseChangeFoam is employed. Large-eddy simulation of cavitating flow over the sphere is compared with the non-cavitating flow at the same Reynolds number. This work provides a thorough understanding of the fluid dynamic characteristics of the sphere cavitation such as vorticity field, turbulent kinetic energy, pressure, velocity, streamlines and boundary layer. Also, detailed analyses of the instantaneous cavity leading edge and separation point location, vortex shedding, streamwise velocity fluctuation and evolution of the cavity are reported. Characteristics of the wake of the cavitating flows are compared with the single-phase results. We report that cavitation suppresses instability in the near wake region and delays the three-dimensional breakdown of the vortices. The volume fraction contours of the cavity cloud obtained from the numerical simulations are compared with the experimental data at the same working condition with a suitable quantitative accuracy.